Study on Nutritional Knowledge, Attitude and Behavior of Chinese School Football Players - Yao Chen; Yingshuang Sun; Zhiyun Liu; Donglin Hu (MDPI AG, 2022)
Objective: This study aims to validate previous structural models of factors influencing dietary behavior changes and construct the knowledge, attitude, and behavioral models of youth school football players. Methods: 279 school football players aged 12-17 years in Grades 7-12 in Hunan Province, China, completed a questionnaire to collect data on sports nutrition knowledge, attitudes, and behavior. A structural equation model (SEM) was built based on the knowledge-attitude-behavior (KAB) model and the theory of planned behavior (TPB) model to introduce nutritional knowledge directly or by altering attitudes into the dietary behavior path of players. Four factors affecting dietary behaviors were involved in the hypothetical structure, which consists of the following hypotheses: (1) nutrition knowledge affects the attitude towards sports nutrition (H1); (2) nutrition knowledge affects dietary behaviors (H2); (3) nutrition knowledge affects subjective norms (H3); (4) nutrition knowledge affects perceived behavioral control (H4); (5) subjective norms affect dietary behaviors (H5); and 6) perceived behavioral control affects dietary behaviors (H6). Results: Confirmatory factor analysis (CFA) revealed that the reliability, convergent validity, and discriminant validity of the built SEM conformed to the measured relationships in each dimension. In the final structural model, it was found that nutrition knowledge had a direct impact on the attitudes of players and affected their dietary behaviors in a direct manner or through their subjective norms and perceived behavioral control. Conclusions: The results are in agreement with the TPB-based KAB chain and support the KAB theory for youth school football players in Hunan Province, China.